Robotic-Assisted Latissimus Dorsi Harvest in Delayed-Immediate Breast Reconstruction - Clemens, Mark W.; Kronowitz, Steven; Selber, Jesse C. (Seminars in Plastic Surgery, 2014)
For two-stage, implant-based, delayed-immediate reconstruction of the radiated breast, robotic-assisted latissimus dorsi harvest (RALDH) is a good option for patients who wish to avoid a traditional latissimus dorsi donor-site incision. The purpose of this study was to compare outcomes of RALDH and the traditional open technique (TOT) for patients undergoing delayed-immediate breast reconstruction following radiation therapy. A retrospective analysis of a prospective database of all consecutive patients undergoing latissimus dorsi harvest for radiated breast reconstruction between 2009 and 2013 was performed. Indications, surgical technique, complications, and outcomes were assessed. One hundred forty-six pedicled latissimus dorsi muscle flaps were performed for breast reconstruction and 17 were performed robotically during the study period (average follow-up 14.6 ± 7.3 mo). Latissimus dorsi breast reconstruction following radiation was performed in 64 patients using TOT and 12 using RALDH. Surgical complication rates were 37.5% in TOT versus 16.7% in RALDH (p = 0.31) including seroma (8.9% versus 8.3%), infection (14.1 versus 8.3%), delayed wound healing (7.8% versus 0), and capsular contracture (4.7% vs. 0). Robotic-assisted harvest of the latissimus dorsi muscle is associated with a low complication rate and reliable results for delayed reconstruction of the irradiated breast while eliminating the need for a donor-site incision.
Keywords: robotic assisted; delayed immediate; latissimus dorsi; radiated breast; breast reconstruction